2010
DOI: 10.1002/icd.711
|View full text |Cite
|
Sign up to set email alerts
|

Do verbal interactions with infants during electronic media exposure mitigate adverse impacts on their language development as toddlers?

Abstract: The goal of this study was to determine whether verbal interactions between mothers and their 6-month-old infants during media exposure (‘media verbal interactions’) might have direct positive impacts, or mitigate any potential adverse impacts of media exposure, on language development at 14 months. For 253 low-income mother–infant dyads participating in a longitudinal study, media exposure and media verbal interactions were assessed using 24-hour recall diaries. Additionally, general level of cognitive stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 52 publications
3
82
1
4
Order By: Relevance
“…19,20 In one longitudinal study of low-income families, 14-month-olds whose mothers had talked with them during educational TV programming since infancy showed more advanced language development than infants whose mothers did not talk with them during media use (although this finding also may have reflected how much mothers spoke to children in general). 21 The few experimental studies showing independent learning of words from videos at this age have been limited by their low ecologic validity 22 or have shown that toddlers lose the knowledge learned over time without repetition. 23 More recent research has shown that, under particular conditions, children between 15 and 24 months of age can learn from repeated viewing of video demonstrations without adult help.…”
Section: At What Age Can Infants and Toddlers Learn From Screens?mentioning
confidence: 99%
“…19,20 In one longitudinal study of low-income families, 14-month-olds whose mothers had talked with them during educational TV programming since infancy showed more advanced language development than infants whose mothers did not talk with them during media use (although this finding also may have reflected how much mothers spoke to children in general). 21 The few experimental studies showing independent learning of words from videos at this age have been limited by their low ecologic validity 22 or have shown that toddlers lose the knowledge learned over time without repetition. 23 More recent research has shown that, under particular conditions, children between 15 and 24 months of age can learn from repeated viewing of video demonstrations without adult help.…”
Section: At What Age Can Infants and Toddlers Learn From Screens?mentioning
confidence: 99%
“…Subsequently, these children could understand the meaning of new words. Similarly, Mendelsohn et al (2010) concluded in their study that media in children's programs constitutes a positive source www.ccsenet.org/jedp Journal of Educational and Developmental Psychology Vol. 5, No.…”
Section: Children and Media Exposurementioning
confidence: 99%
“…Mendelsohn et al (2010) concluded that the absence of in-person interaction during media exposure showed an absence of educational benefits in two-year-old children. In a study conducted on 61 toddlers, Barr and Wyss (2008) examined the notion of whether label along with voiceover is presented in children's educational programs to facilitate imitation.…”
Section: Children's Interaction and Media Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…During both the home visit and the telephone calls, case managers used their training to try to motivate and empower parents to replace violent and age-inappropriate media content with content that was age-appropriate and educational or prosocial in nature. Parents also were encouraged to engage in co-viewing and to discuss media content with their children, because co-viewing can increase parent awareness of the media content consumed, and some evidence suggests that co-viewing or discussion may enhance the positive effects of educational and prosocial media, 30,31 although it may not mitigate the negative effects of violent or scary media. 32 The monthly mailings included a program guide tailored to the family' s available channels with recommended educational and prosocial television shows and schedules and a newsletter with tips and reinforcement.…”
Section: Interventionmentioning
confidence: 99%